UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN SIRSAK (Annona muricata Linn.) TERHADAP MENCIT (Mus musculus) JANTAN YANG DIINDUKSI DENGAN KARAGEN - Rahmawati Rahmawati; Safriani Rahman; Mustari Mustari (Fakultas Farmasi UMI, 2012)
The research about aniinflammatory effect of Sirsak leaves (Annona muricata Linn.) ethanolic extract in male mice (Mus musculus) was conducted, the aim to assay the anti-inflammatory effect of Sirsak leaves done extract based on decrease in oedema volume of foot palm male mice. It was used 15 male mices that evaluated and divided into 5 groups that each group has 3 mices given extract in dose 0f 0,182 g/kgBB, 0,546 g/kgBB and 0,91 g/kgBB, one group as the compore which administered diclofenac sodium, one negative control group which administered 1% Na.CMC. induction carried out by injection 1% w/v carrageen 0,05 ml subcutan in the feet palm of mice. One hour later each group administered the teste preparation orally 1 ml/30 gBW. Group 1 to 3 the series dose of the extract 0,182 g/kgBB, 0,546 g/kgBB and 0,91 g/kgBB. Group 5 diclofenac sodium suspension. The measurement of oedema volume carried out prior and after administration of the tested preparation 0, 30, 60, 90, and 120 minutes. The data correlation between oedema versus time analysed value with use SPSS 20.Result indicated variaties with ethanolic Extract of Sirsak leaves have the effect antiinflamatory at dose 0,182 g/kgBB, 0,546 g/kgBB, dan 0,91 g/kgBB and not differ the reality by Natrium Diklofenak.Keywords : Inflamation, Anona muricata’s leaf, Carageen.